Managerial Expertise, Private Information, and Pay-Performance Sensitivity - Dutta, Sunil (Management Science, 2008)
This paper characterizes optimal pay-performance sensitivities of compensation contracts for managers who have private information about their skills, and those skills affect their outside employment opportunities. The model presumes that the rate at which a manager's opportunity wage increases in his expertise depends on the nature of that expertise, i.e., whether it is general or firm specific. The analysis demonstrates that when managerial expertise is largely firm specific (general), the optimal pay-performance sensitivity is lower (higher) than its optimal value in a benchmark setting of symmetric information. Furthermore, when managerial skills are largely firm specific (general), the optimal pay-performance sensitivity decreases (increases) as managerial skills become a more important determinant of firm performance. Unlike the standard agency-theoretic prediction of a negative trade-off between risk and pay-performance sensitivity, this paper identifies plausible circumstances under which risk and incentives are positively associated. In addition to providing an explanation for why empirical tests of risk-incentive relationships have produced mixed results, the analysis generates insights that can be useful in guiding future empirical research.